Primary cutaneous melanoma of the scalp: Patterns of recurrence. Issue 4 (30th December 2016) - Sparks, David S.; Read, Tavis; Lonne, Michael; Barbour, Andrew P.; Wagels, Michael; Bayley, Gerard J.; Smithers, B. Mark
Abstract : INTRODUCTION: Patients with primary melanoma of the scalp have been reported to have worse disease‐related outcomes compared with other anatomical regions. There are few studies in the literature specifically addressing recurrence patterns and treatment outcomes for primary scalp melanoma as a discrete anatomical sub‐region. We sought to identify key features adversely influencing disease control and survival and to clarify the role of resection plane, margin, and method of reconstruction in the management of this disease process. METHODS: A retrospective clinical study of medical records was performed evaluating all patients with primary melanoma of the scalp treated at two hospitals in southeast Queensland between 2004 and 2014. RESULTS: A total of 107 patients were eligible for analysis. There were 46 recurrences in 38 patients in the cohort accounting for a recurrence rate of 35.5%. The local recurrence rate was 15.9% with 12 in‐transit metastases after diagnosis. Regional and distant recurrence rates were 12.1% and 15%, respectively. At a median follow up of 30.5 months, disease‐free survival was 47% and overall survival was also 47%. On multi‐variate analysis, the deeper resection plane (sub‐galeal) had a lower disease‐free survival rate compared with the supra‐galeal resection plane ( P = 0.032). DISCUSSION: Our results support the hypothesis that primary scalp melanoma represents a unique aggressive subcategory with high rates of in‐transit disease and poor disease‐related and survival outcomes. There is a need for robust prospective comparative studies to address the significance of resection plane in the management of patients with scalp melanoma.